Posisi Geopolitik Indonesia dalam Konteks Hubungan Regional Asia Tenggara - Sugiharto Sugiharto; Mulhady Putra; As-Syifa R.Ramdhani Tanjung; Siti Hajar Sahari (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Indonesia has a very strategic geopolitical position as the largest archipelagic country in the world located at the intersection of two continents and two oceans. This geographical location gives Indonesia an important role in the political, economic, and security dynamics of the Southeast Asian region as well as in the global system. This study aims to analyze Indonesia's geopolitical position and its role in regional relations, especially in the ASEAN region. The method used is qualitative-descriptive with a literature study approach. The results of the study show that Indonesia has great potential as a regional leader through multilateral cooperation, strengthening diplomacy, and the vision of the World Maritime Axis. However, Indonesia also faces challenges such as territorial disputes, pressure from global powers, economic inequality, and environmental issues. Therefore, an adaptive and active foreign policy strategy is needed to strengthen Indonesia's position in the geopolitical chessboard of the region and the world.